Organizational Justice and Citizenship Behaviors: The Mediating Role of Job Satisfaction across OCBI and OCBO - Muhammad Fitrah Panabari Nasution; Zaitul; Listiana (Journal of Educational Management Research, 2026)
This study examines the relationship between organizational justice and Organizational Citizenship Behavior (OCB), focusing on Organizational Citizenship Behavior toward Individuals (OCBI) and toward the Organization (OCBO), with job satisfaction as a mediating variable. The research was conducted at TVRI West Sumatra, a public broadcasting institution in Indonesia. Using a census approach, data were collected from 130 employees and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that organizational justice has a positive and significant effect on job satisfaction, OCBI, and OCBO. Job satisfaction also significantly influences both OCB dimensions. Mediation analysis confirms that job satisfaction partially mediates the relationship between organizational justice and citizenship behavior. The hierarchical component model further demonstrates that OCB is a second-order construct, with OCBO contributing more strongly than OCBI. Importance–Performance Map Analysis reveals that organizational justice exerts a slightly stronger total effect on organization-directed citizenship behavior. Overall, the results highlight organizational justice as a strategic determinant of employee attitudes and voluntary performance, particularly in public sector institutions where collaboration and institutional commitment are essential for sustaining organizational effectiveness.